Analisis Pengaruh Ketidakseimbangan Beban Terhadap Efisiensi Transformator Distribusi - Jeri Arnando; Amir Hamzah; Feranita Feranita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The increasing user of electrical energy so PT PLN (Persero) is required to design a balanced distribution of electric power in each phase, in order to meet the needs of efficient electricity. However, there is often a load imbalance in the distribution of electric power. This study analyzes the effect of load imbalance on distribution transformer efficiency by using the calculation method of percentage loading, load imbalance, losses and efficiency of the transformer. From the results of the study it was found that the lowest efficiency occurs when the load imbalance is high. So that in this condition the neutral wire will have a current and cause losses where the value is proportional to the value of the neutral current. These energy losses will lead to lower transformer efficiency. From the results of research that has been carried out on the distribution transformer of PLN (Persero) ST 009 on October 29, 2021 with data obtained at 21.00, the load imbalance is 10.88% with a neutral current of 96 A and at 22.00, the load imbalance- it is 7.2% and the neutral current is worth 74 A. So the losses that occur at 21.00 are greater than at 22.00 which results in efficiency at 21.00 being smaller than at 22.00 with efficiency values of 94.41% each. compared to 95.04%. Keywords: Load Unbalance, Loss, Transformer Efficiency.